A New Decavanadate with Organic Cation: Synthesis, Crystal Structure, and Hirshfeld Surface Analysis - Rawia Nasri; Regaya Ksiksi; Mohsen Graia; Mohamed Faouzi Zid (Advances in Materials Science and Engineering)
A new 2,6-bis aminomethyl piperidine decavanadate hydrate, (C7N3H20)2V10O28.4.21H2O, was synthesized by slow evaporation of a solution at room temperature. The molecular structure was investigated by single-crystal X-ray diffraction. In the crystal structure, the layers of decavanadate groups, organic cations, and water molecules are arranged parallel to the (010) plane. Also, the prepared compound has been analysed by FTIR spectroscopy and scanning electron microscopy (SEM). The crystal structure of the title compound is stabilized by hydrogen bonds and van der Waals interactions. The cohesion of the structure is ensured by O-H…O and N-H…O hydrogen bonds. The three-dimensional Hirshfeld surface (3D-HS) and the relative two-dimensional fingerprint plots (2D-FPs) of (C7N3H20)2V10O28.4.21H2O compound revealed that the structure is dominated by O…H/H…O (70.8%) and H…H (18.5%) contacts.